2021
DOI: 10.1186/s12979-020-00212-x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and COVID-19: what makes obese host so vulnerable?

Abstract: The disease (COVID-19) novel coronavirus pandemic has so far infected millions resulting in the death of over a million people as of Oct 2020. More than 90% of those infected with COVID-19 show mild or no symptoms but the rest of the infected cases show severe symptoms resulting in significant mortality. Age has emerged as a major factor to predict the severity of the disease and mortality rates are significantly higher in elderly patients. Besides, patients with underlying conditions like Type 2 diabetes, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
144
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(161 citation statements)
references
References 135 publications
9
144
0
8
Order By: Relevance
“…Almost immediately after the pandemic outbreak in China, greater vulnerability and higher incidence of severe clinical presentation and fatal outcome were observed in patients with particular preexisting conditions, especially in persons aged > 65 1,2 . Numerous studies have shown that the greatest risk of severe COVID-19 course/manifestation is posed by the presence of either diabetes mellitus, obesity, arterial hypertension or immunosuppression / immunodeficiency [3][4][5][6][7][8] . Severe COVID-19 manifestations include development of extensive bilateral pneumonia, ARDS and endothelial damage accompanied with accelerated thrombogenesis, which can all lead to the respiratory and multiorgan failure, being major clinical concern due to intensive care units overcrowding and high mortality rate 4,6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost immediately after the pandemic outbreak in China, greater vulnerability and higher incidence of severe clinical presentation and fatal outcome were observed in patients with particular preexisting conditions, especially in persons aged > 65 1,2 . Numerous studies have shown that the greatest risk of severe COVID-19 course/manifestation is posed by the presence of either diabetes mellitus, obesity, arterial hypertension or immunosuppression / immunodeficiency [3][4][5][6][7][8] . Severe COVID-19 manifestations include development of extensive bilateral pneumonia, ARDS and endothelial damage accompanied with accelerated thrombogenesis, which can all lead to the respiratory and multiorgan failure, being major clinical concern due to intensive care units overcrowding and high mortality rate 4,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with risk factors more likely react with extremely excessive systemic inflammation resulting with cytokine storm which is considered as an executive pathophysiological mechanism responsible for severe disease manifestations, such as acute respiratory distress syndrome (ARDS), diffuse endothelial damage with accelerated thrombogenesis and multiple organ dysfunction syndrome (MODS) 6 . In most groups of risk patients, common mechanism favoring development of excessive inflammation and cytokine storm is persistently present proinflammatory milieu 7 . Such chronic proinflammatory state can arises either due to hypersecretion of proinflammatory adipokines in obese patients 7 , lack of anti-inflammatory signaling in diabetic and insulinresistant patients 7,8 or dysregulation of renin angiotensin system (RAS) with increased proinflammatory angiotensin II (Ang II) production in hypertensive patients 6,9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, in January 2020, the disease's first cases were reported outside China (one in Japan and two in Thailand). Since then, the disease has spread rapidly to all countries of the world [114,115]. The condition was declared a pandemic on 11 March 2020, by WHO on 11 March 2020, and to date (22 February 2021), the total number of infected patients has reached 112,045,556, of which 2,479,625 people lost their lives (https://www.worldometers.info/coronavirus/, accessed on 20 February 2021).…”
Section: Nafld and Osmentioning
confidence: 99%
“…As mentioned, obesity is directly related to COVID-19 disease and leads to increased inflammation, mitochondrial dysfunction, and increased ACE2 receptors. Numerous studies have shown that high BMI (≥30 kg/m 2 ) and excess visceral fat (VF) are effective methods in diagnosing the severity of COVID-19, especially in obese patients [115,119,121].…”
Section: Nafld and Osmentioning
confidence: 99%